Peningkatan Kosa Kata Bahasa Inggris Anak Usia 5-6 Tahun Pada Pembelajaran Menggunakan Media Flashcard - Khania Zalfa Mozalica Putri; Edi Hendri M; Alfian Azhar Y (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to improve the English vocabulary of children aged 5-6 years through flashcard-based learning at TK Kartika IX-10. The probelm addressed is the low mastery of English vocabulary due to unengaging learning methods and lack of visual media. The research employed a Classroom Action Research (CAR) model by John Elliot consisting of three cycles with planning, action, observation, and reflection stages. The subjects were 12 children from group B2. Data were collected through observation, documentation, and pretest-posttest assessments. The findings indicates a significant improvement in vocalbulary mastery, from a pre-action average score of 42,5%, increasing to 56,25% in cycle I, and reaching 83,75% in cycle II. Teachers’s abilities in planning and implementing instruction also improved through better lesson planning and more engaging media use. In conclusion, the use of flashcard media was proven effective in enhancing early childhood English vocabulary. The implications suggest that integrating visual media like flashcards supports foreign language development in young learners in a fun and meaningful way